Myth: Dementia is a Normal Part of Aging - Dobrowolski, Chrisanna (DALHOUSIE MEDICAL JOURNAL, 2014)
It is commonly assumed that cognitive function deteriorates with age. While some age-related changes in cognitive function exist, they do not exist to the extent that is widely believed. The pathologic changes seen in patients with dementia differ significantly from those seen in healthy elderly persons. Additionally, many seniors exhibit virtually no changes at all and continue to lead fruitful lives well beyond the average life expectancy. There are important implications of assuming that dementia is a normal part of aging: this myth contributes to poorer cognitive performance in seniors, to stigma and to a lack of initiative in preventing cognitive decline. Here the author demonstrates the prevalence of this myth and then challenges it, taking into account current evidence regarding normal age-related cognitive changes and pathologic cognitive changes as seen in patients with dementia.